Meningkatkann Kemampuan Membaca Al-Qur’an melalui Metode Al-Barqi pada Siswa Kelas VIII di MTs Al-Magfirah Cikarang Barat Bekasi - Zaini, Zaini; Afif, Nur (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to find out how to improve the ability to read the Al-Qur'an through the Al-barqy method in class VIII students at MTs Al Magfirah. This research uses a classroom action model with the Kemmis and Mc model. Taggart. The research sample consisted of 30 students with several stages, namely, action planning, action implementation with cycles I-II of corrective action through observation sheets and oral tests, as well as reflection on the results of actions on the progress that has been obtained from corrective action.From the results of the research and discussion of the research results, it can be concluded that there has been an increase in the ability to read the Al-Quran through the Al-Barqy method in Islamic religious education subjects with the theme of hijaiyah letters in class VIII Madrasah Tsanawiyah Al-Maghfirah West Cikarang, Bekasi Regency. It can be concluded that there has been an increase of each indicator of reading the Al-Quran at the level of Starting to Developing Medium, with the form of improvement through the application of the Al-Barqy method, namely, being able to read hijaiyah letters which are almost the same in sound and shape, being able to read and connecting hijaiyah letters, being able to read the Al-Quran with mad (long) reading, and can read the Al-Quran with fathah tanwin. Increasing Al-Quran reading through the Al-Barqy method has an average percentage increase of 32.80% -50% which is included in the Medium Developing level.